Global economic crisis: Employee responses and practical implications for organizations - Naude, Marita; Dickie, Carolyn; Butler, Bella (Organization Development Institute, 2012)
The global economic crisis of 2008 created rapid social and economic change which shook the foundations of major economies and demanded immediate response; both organizations and employees had to adapt. This study, which formed the basis for this paper, was conducted in Western Australia with the aim of discovering how employees responded to the changed work environment and how organizations managed employee responses. A single case design was used and key findings suggest that organizations responded to the economic crisis through a range of human resource management changes. Employees experienced a range of responses from limited to major uncertainty and voiced both negative and positive responses regarding the way in which their organization responded. As a practical contribution, the authors offer guidelines based on the change model by Kotter (2007) that could be used by organizations facing similar situations.